Prognosis of distal pancreatic cancers controlled by stage - Luo, Guopei (Exp Ther Med, 2020)
Patients with distal (body/tail) pancreatic cancer have been found to present worse outcome than patients with head cancer, which is generally attributed to the great proportion of advanced stages for body/tail cancers upon detection. However, differences in prognosis between head and body/tail pancreatic cancers controlled by stage have not been analyzed in-depth. In this study, differences in prognosis between head and body/tail pancreatic cancers were examined using the Surveillance, Epidemiology, and End Results Program (SEER) (1973-2014 registry, 85,715 cases). We found that patients with body/tail pancreatic cancer had worse prognosis than patients with head cancer for all combined stages [adjusted hazard ratio (HR), 1.03, 95% confidence interval (CI), 1.00-1.05, P=0.025]. Compared with patients with head cancer, patients with body/tail cancer had lower mortality for stage I cancers (HR, 0.85, 95% CI, 0.76-0.94, P=0.001), no difference in mortality for stages II or III (stage II, HR, 1.00, 95% CI, 0.95-1.06, P=0.965; stage III, 0.97, 95% CI, 0.91-1.04, P=0.398), and higher mortality for stage IV (HR, 1.07, 95% CI, 1.04-1.10, P<0.001). In addition, the proportion of body/tail pancreatic cancer increased from 24.9% in 1973 to 36.3% in 2014. Therefore, tumor location of body/tail is an independent adverse prognostic factor for patients with pancreatic cancer. However, this observation is not applicable when controlled by stage (body/tail versus head pancreatic cancer, better stage I, similar stage II/III, and worse stage IV).